1991
DOI: 10.1001/archderm.1991.01680050083008
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Epidermal Necrolysis and Stevens-Johnson Syndrome

Abstract: Little work has been carried out on the epidemiology of the two serious skin reactions--toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS). We collected details of all the hospitalized cases of TEN and SJS in the Federal Republic of Germany for the years 1981 through 1985 inclusive. Inquiries by telephone, letter, and personal visits produced an overall response of 91%; 259 cases of TEN and 315 cases of SJS were identified. From these data, we were able to calculate an overall annual risk of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(59 citation statements)
references
References 8 publications
1
53
1
Order By: Relevance
“…In most of these studies with the exception of Togolese one, these drug reactions were attributable to thiacetazone. In addition, unlike the European and Asian studies [12] [13] [17] [18], drugs against gout, such as allopurinol, were not found in African studies except ours where this molecule was found in 3 cases, probably due to its low use by people in Africa [19]. Furthermore, no infectious cause was found in our patients because of the non-realization of mycoplasma serology, PCR and blood culture.…”
Section: Discussioncontrasting
confidence: 63%
“…In most of these studies with the exception of Togolese one, these drug reactions were attributable to thiacetazone. In addition, unlike the European and Asian studies [12] [13] [17] [18], drugs against gout, such as allopurinol, were not found in African studies except ours where this molecule was found in 3 cases, probably due to its low use by people in Africa [19]. Furthermore, no infectious cause was found in our patients because of the non-realization of mycoplasma serology, PCR and blood culture.…”
Section: Discussioncontrasting
confidence: 63%
“…[1,2] It is 1.1 and 0.93 per million per year for SJS and TEN respectively in Germany. [3] Drugs are most commonly implicated for causing 77-95% of cases. [4,5] SJS/TEN have been observed with more than 100 drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] The mortality rate of SJS and TEN is high; approximately, 5% for SJS [4] and 30% for TEN. [5] Now SJS, SJS-TEN overlap and TEN are considered a spectrum of the same condition having common risk factors and causes, differentiated only by the extent of the body surface area (BSA) involved. Patients with epidermal detachment involving less than 10% of BSA are classified as having SJS, more than 30% BSA as TEN and 10-30% as SJS/TEN overlap.…”
Section: Introduction Introductionmentioning
confidence: 99%